Taxonomical Analysis of Agricultural Modernity of Farmers - Sreevalsan J Menon (Department of Agricultural Extension, College of Agriculture, 1995)
This study was undertaken based on the premise that any attempt to design a suitable extension strategy for modernizing agriculture requires a through understanding of the individual modernity of a farmer. The study area was the Perumbazhuthoor Panchayat and a sample of 120 farmers were randomy selected. The data were collected with the help of a pre-tested interview schedule and suitable statistical tests were applied. The main findings of the study were as follows: Among the four components viz., socio-psychological behaviour, adoption behaviour, communication behaviour and economic behaviour, adoption behaviour received maximum weight. Nine items (determinants) were selected out of 18 items proposed across the four components. The number of determinants were three under socio-psychological behaviour and two each under adoption, communication and economic behaviour. A composite agricultural modernity index was developed with the nine determinants viz., education, attitude towards scientific cultivation, knowledge, adoption of improved practices, innovativeness, information source utilisation, information dissemination behaviour, economic motivation and management orientation. Increase in the nine determinants viz., education, attitude towards scientific cultivation, knowledge, adoption of improved agricultural practices, innovativeness, information source utilization, information dissemination behaviour, economic motivation and management orientation enhanced CAMI. For every five unit increase in each of the determinants namely education, attitude towards scientific agriculture, knowledge, adoption of improved agricultural practices innovativeness, information source utilization, information dissemination behaviour, economic motivation and management orientation, there was one unit increase in CAMI. Nearly two third of the total respondents belonged to the medium modernity level. None of the categories of farmers came under very high modernity level. Two third of the farmers under Category I, II, III belonged to the medium modernity level, and nearly one fourth belonged to the high modernity level. None of the farmers under Category III came under the low modernity level. Almost half of the respondents had high levels of satisfaction and calculability but had low levels of social participation. Nearly two third of the farmers were less environmentally oriented and less fatalistic. Increase in the psychographics, viz., satisfaction, calculability, social participation and environmental orientation enhanced CAMI and a decrease in fatalism enhanced CAMI. For every three unit increase in satisfaction, there was two unit increase in CAMI ceterisparibus. For every one unit decrease in fatalism ceterisparibus, there would be one unit increase in CAMI. For every two units increase each in calculability and social participation ceterisparibus, there were three units increase and one unit increase in CAMI respectively. For every one unit increase in environmental orientation, there were two units increase in CAMI ceterisparibus. Increase in the factors viz., farm size, number of enterprises, credit behaviour, cosmopoliteness, training and risk orientation increased CAMI and a decrease in farming experience increased the CAMI. For every one unit increase each in cosmopoliteness, training and risk orientation there was one unit increase in CAMI ceterisparibus.